Understanding the impact of eWOM communication through the lens of information adoption model: A meta-analytic structural equation modeling perspective - Yogesh Dwivedi (Computers in Human Behavior, 2023)
In the last decade, eWOM has arguably become the most preferred way for consumers to seek and share consumption-related information. eWOM as a research topic also garnered huge attention from the research community, which led to the vast academic literature on eWOM. However, there is a lack of consensus on how different eWOM attributes impact consumer responses to eWOM communication. Moreover, there is also inconsistency regarding the mechanism through which eWOM messages influence consumers' behavioral intentions. To address this gap, we conduct a meta-analysis of 179 studies comprising 186 unique samples and 65,655 observations, which reveals the strength and significance of the association between eWOM attributes and eWOM response. Further, based on the Information Adoption Model, this study investigates the various mechanisms through which eWOM credibility, eWOM usefulness, and attitude towards eWOM impact purchase intention. In addition, this study discusses the moderating role of culture, product and platform type. Results of meta-analytic structural equation modeling (MASEM) support a serial mediation model of eWOM credibility and attitude towards eWOM on purchase intention through eWOM usefulness and eWOM adoption. From the research perspective, this study resolves the inconsistencies in the extant literature to provide more reliable generalizations. Managers can use this study to enhance the consumers’ purchase intention through effective management of eWOM communication.